Electrodeposition of Pt-Decorated Ni(OH)2/CeO2 Hybrid as Superior Bifunctional Electrocatalyst for Water Splitting - Huanhuan Liu; Zhenhua Yan; Xiang Chen; Jinhan Li; Le Zhang; Fangming Liu; Guilan Fan; Fangyi Cheng (Research, 2020)
The facile synthesis of highly active and stable bifunctional electrocatalysts to catalyze water splitting is attractive but challenging. Herein, we report the electrodeposition of Pt-decorated Ni(OH)2/CeO2 (PNC) hybrid as an efficient and robust bifunctional electrocatalyst. The graphite-supported PNC catalyst delivers superior hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) activities over the benchmark Pt/C and RuO2, respectively. For overall water electrolysis, the PNC hybrid only requires a cell voltage of 1.45 V at 10 mA cm−2 and sustains over 85 h at 1000 mA cm−2. The remarkable HER/OER performances are attributed to the superhydrophilicity and multiple effects of PNC, in which Ni(OH)2 and CeO2 accelerate HER on Pt due to promoted water dissociation and strong electronic interaction, while the electron-pulling Ce cations facilitate the generation of high-valence Ni OER-active species. These results suggest the promising application of PNC for H2 production from water electrolysis.